Zygmunt Spira's remarks on Popper's methodology - Polak, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2006)
The paper presents an outline of the reception of Popper's thought in Poland in the period between two World Wars. The most important paper in this period is doubtlessly the one published by Zygmunt Spira entitled 'Remarks on Popper's methodology and epistemology'. Spira was a student of Z. Zawirski. He lived and worked in Cracow, and was killed during the Nazi occupation. His paper is by now forgotten. We critically present his main ideas, showing his innovatory style of thinking.